Survey of learning activities for mild mentally retarded children in physical education learning - Ayu Nida Nur Rahmania; Basuki Basuki (Sriwijaya Journal of Sport, 2021)
This study aims to determine the learning activity of mild mentally retarded students in learning adaptive physical education in the new normal period. The survey method was carried out in this study to find out the active data of students. The data collection technique used an assessment instrument in the form of a checklist by means of learning observation. The results of this study indicate that observations were made twice, the highest percentage was 56.25% of students who were active in the learning process with indicators always active getting a percentage of 33.25%, sometimes active 19.50%, and inactive at 3.50%. Based on the results of the research that has been done, it can be concluded that the level of activity of mentally retarded students in participating in adaptive physical education learning at SLBN Jombang can be said to be active.